"Showing Everybody's True Colors": Informal networks of low-income single mothers and their young children during the COVID-19 pandemic. (June 2022) - Radey, Melissa; Lowe, Sarah; Langenderfer-Magruder, Lisa; Posada, Kristine
Highlights: Low-income mothers turned to their networks and exchanged support during COVID-19. Although emotionally valuable, networks could not meet increased economic and child care needs. The pandemic's economic and time use impacts tested network relationships. Relationships strengthened or dissolved due to network members' COVID-19 responses. Abstract: Extensive evidence suggests low-income mothers depend upon their families and friends for emotional, practical, and economic support in times of need. This is the first study to examine the operation of low-income mothers' informal support networks and the impact of such networks on maternal well-being during the COVID-19 pandemic. We interviewed low-income, single mothers of young children (<12 years; N  = 34) twice over Summer 2020 to consider mothers' decisions around network engagement and how their interactions contributed to their well-being. Consistent with the social capital framework and previous studies, most mothers turned to their networks and exchanged support. Thematic analysis uncovered 4 inter-related themes of mothers' experiences: (1) discovering emotionally-available networks, (2) navigating resource-limited networks, (3) reassessing network member relationships, and (4) establishing boundaries for in-person contact. Although emotionally valuable, networks could not meet increased economic and child care needs. The COVID-19 pandemic's economic impact and its impact on time use tested network relationships with some relationships strengthening and others dissolving. Widely-available emotional support was essential to mothers adapting to the pandemic. Safe, affordable child care options coupled with accessible, economic supplements can promote well-being among single mothers and their children.